Changing marriage and divorce rate in Poland compared to other EU countries. - Barański, Tomasz; Kaczmarek, Sylwia (Bulletin of Geography. Socio-economic Series, 2007)
This article focuses on recent tendencies concerning marriages and divorces in the EU Member States and in Poland, including the trends observable in the Province of Lodz broken down by county as a case study. Consideration is given to the factors determining a decline in the number of marriages and an increase in the number of divorces. Additionally the problem of postponing the decision to marry and entering into marriage by men and women at an increasingly later age is discussed.